The Effects Of Job Stress On Wellbeing And Medical Professionalism Among Doctors At Public Hospitals In Hebei Province, China: The Moderating Role Of Humor - Qi, Fang Shu (2019)
Job stress has been known as a major cause of well-being and work outcome among medical doctors in hospitals. However, the previous study on stress management among doctors in China still has received a little intention. Hence, this study intends to examine the relationship between job stress, workload, work environment, physical-ill health, mental-ill health and medical professionalism. In addition, it also examines the role of humor as moderation effect on the relationship among job stress, physical-ill health, mental-ill health and medical professionalism. Survey Questionnaire has been distributed to the medical doctors at public hospitals of Hebei Province, China. All of data was analysed by using structural equation modeling (SEM) via partial least square (PLS). Findings indicated that workload had significant impact on job stress, work environment had no significant impact on job stress. Job stress had positive significant direct relationship on physical-ill health and mental-ill health, however it showed negative relationship between job stress and medical professionalism. Humor did not moderate the relationship between job stress and its outcomes (physical-ill health, mental-ill health and medical professionalism).